Isomeric DTPA-amide macrocycles of p-xylenediamine and their complexation with Gd3+. (28th May 2015) - Navarro, Rosa Elena; Soberanes, Yedith; D-Yañez, Sheyla; Jatomea, Olivia; Ramírez, José Zeferino; Inoue, Motomichi
Graphical abstract: Three macrocycles have been isolated from reactions between DTPA dianhydride and p -xylenediamine: a 2 + 2-cyclization macrocycle in a high yield, and two 1 + 1-macrocyclic isomers which differ in coordination capability toward Gd 3+ . Abstract: Three DTPA-amide cyclophanes – including conformational isomers – have been isolated by optimizing the conditions of a reaction between diethylenetriaminepentaacetic (DTPA) dianhydride and p -xylenediamine: a 2 + 2-cyclization product, abbreviated as (cy2)H6, that integrates two phenylene groups in the macrocyclic frame and bears six pendant –CH2 CO2 H arms, and two isomeric 1 + 1-macrocyles, (cy1)H3, carrying three arms. A crucial factor for controlling the ring size is the concentration in the reaction. For (cy2)H6, whose binuclear Gd 3+ complex is a potential paramagnetic protein sensor, the synthetic method has been established in 70% yield. The isomerism of (cy1)H3 is due to the conformation of the rigid macrocyclic frame; the 1 H NMR and geometry optimization show that the conformation is of quasi-C2 symmetry in one (cy1)H3 isomer, and of quasi-mirror symmetry in the other. Their distinct conformations define the chemical properties and coordination capability toward Gd 3+ : in the C2 -symmetric isomer, the amino nitrogen is less basic and the N–H bond is more covalent than in the mirror-symmetric isomer; the former forms a mononuclear Gd 3+ complex whereas the latter does not show sign of complexation with Gd 3+ .